Excess Body Mass Exacerbates the Association Between Poor Physical Function and Frailty in Older Community Dwelling Adults - Mahta Hayati MSc; Parvaneh Nazarali PhD; Mahta Sardroodian PhD; Hunter Bennett PhD; Mahdi Hosseinzadeh PhD (SAGE Publishing, 2024)
Numerous measures of physical function have been shown to be independently associated with frailty in older adults. This cross-sectional observational study aimed to identify the association between tests of physical function and frailty in community dwelling older adults and explore whether being overweight or obese increases the strength of this association. Mobility, balance, strength performance, and frailty status of 161 community dwelling older adults was measured. Logistic regression examined the association between these measures and frailty status. Participants with both poor performance on these measures (bottom 25% of performance within the cohort) and identified as being overweight or obese (body mass index [BMI] > 24.99) were compared to the rest of the cohort to identify whether weight status exacerbated the strength of these associations. Individually, BMI (odds ratio [OR]= 1.1, 95% CI = 1.0, 1.2; P  = .030, trivial effect ) and poor timed up and go (TUG) performance (OR = 1.5, 95% CI = 1.2, 1.7; P  ≤ .001, small effect ) were associated with frailty. Combinations of excess body mass and poor TUG (OR = 3.7, 95% CI = 1.5, 9.4; P  = .006, moderate effect ), balance (OR = 7.2, 95% CI = 2.3, 22.3; P  = .001, large effect ), mobility (OR = 3.7, 95% CI = 1.9, 7.4; P  ≤ .001, moderate effect ), and upper (OR = 4.5, 95% CI = 2.2, 9.2; P  ≤ 001, large effect ), and lower-body (OR = 3.7, 95%CI = 1.6, 8.5; P  = .003, moderate effect ) strength performance were significantly associated with frailty, as was being female (2.5, 95% CI = 1.3, 4.8; P  = .005, moderate effect ). Poor function and a high body mass are strongly associated with frailty and should be considered important qualities to assess when considering targeted frailty prevention strategies.